2019
DOI: 10.1177/1044389419862081
|View full text |Cite
|
Sign up to set email alerts
|

Like a Blanket Over a Fire: Group Work and Spiritual Repair in Military Trauma

Abstract: Posttraumatic stress disorder (PTSD) may not fully explain why some who experience war feel as though their assumptive world and sense of meaning has been shattered. Two concepts mentioned in the literature that address this feature of trauma are moral injury and spiritual injury. This work reports on qualitative findings from postgroup interviews with 18 participants who completed a spiritually integrated eight-session group intervention known as Search for Meaning. The group is designed to deal directly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…The fact that patients reported mixed success in their search for moral and spiritual healing invites realism about SERT dynamics in treatment for trauma and ongoing questions about factors that might account for differential outcomes. Interviews with patients following the group intervention also revealed the important role of relational dynamics between group leaders and patients, many of whom had suffered betrayals by authority figures in the military (Starnino et al, 2020). This project also offered the relatively unique clinical practice of therapist and chaplain collaboration, which some patients described as helpful to their treatment.…”
Section: Synthetic Review Of the Practice-based Evidencementioning
confidence: 99%
“…The fact that patients reported mixed success in their search for moral and spiritual healing invites realism about SERT dynamics in treatment for trauma and ongoing questions about factors that might account for differential outcomes. Interviews with patients following the group intervention also revealed the important role of relational dynamics between group leaders and patients, many of whom had suffered betrayals by authority figures in the military (Starnino et al, 2020). This project also offered the relatively unique clinical practice of therapist and chaplain collaboration, which some patients described as helpful to their treatment.…”
Section: Synthetic Review Of the Practice-based Evidencementioning
confidence: 99%
“…A preliminary evaluation of 24 US veterans completing the Search for Meaning Program at the VA Medical Center found significant improvements in PTSD symptoms, spiritual injury and negative religious coping (Starnino et al, 2019 ). A qualitative study involving interviews with 18 US veterans following completion of the Search for Meaning Program reported that the veterans found the intervention to be helpful but not sufficient to enable them to make meaning from their PMIE (Starnino et al, 2019 , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, existing PTSD treatments might not be designed to attend to moral injury developing from certain combat or non-combat experiences including remote combat theatre , military sexual assault (Hamrick et al, 2022;Maguen et al, 2022), or acts for which no one is to blame (Fleming, 2021). Thus, moral injury might extend beyond bioneurological effects (Starnino et al, 2020) into the moral realm (Litz et al, 2009) in ways that treatments for PTSD may not address the diverse trauma needs of veterans.…”
Section: Moral Injury Treatmentsmentioning
confidence: 99%